As-synthesized TEA-BEA zeolite: Effect of Si/Al ratio on the Knoevenagel condensation - Chaves, Thiago F.; Pastore, Heloise O.; Hammer, Peter [UNESP]; Cardoso, Dilson (Elsevier B.V., 2015)
The zeolite with BEA structure has been obtained using different Al amounts in the presence of tetraethylammonium as a structure directing agent. The effect of the Si/Al molar ratio on the crystal size, morphology, yield, chemical composition and catalytic properties was investigated. The materials have been characterized towards zeolitic properties by XRD, SEM, EDS, TGA, Si-29 MAS-NMR, XPS and TEM. The chemical composition of the crystals depends on the concentration of the initial reaction mixture and that a decrease in the Al content is associated with an increase in particle size. The characterization by TGA/DTA of as-synthesized zeolites with BEA structure showed that an increase of Si content resulted in the formation of [=Si-O-][TEA(+)] species, this was supported by Si-29 MAS-NMR. The XPS results also showed that the chemical composition of the surface differed from that of the bulk material, this was supported by TEM/EDS results. The results of catalytic activity tests indicated that a fraction of the [=Si-O-][TEA(+)]species was present on the external surfaces of the crystals, although the largest fraction appeared to be in the interior of the particles. As-synthesized BEA zeolite showed good catalytic activity and suggests that this material can be applied in other reactions involving basic sites. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Hydrothermal synthesis; BEA structure; Siloxy species; Basic catalysis; Knoevenagel condensation